Impact of hereditary pancreatitis on patients and their families. Issue 6 (5th February 2020) - Shelton, Celeste A.; Grubs, Robin E.; Umapathy, Chandraprakash; Yadav, Dhiraj; Whitcomb, David C.
Abstract: Hereditary pancreatitis (HP), a highly penetrant (~80%) autosomal dominant disease associated with PRSS1 variants, causes acute pancreatitis in childhood and chronic pancreatitis by early adulthood. Other clinical features include pain, diabetes, and risk of pancreatic cancer. HP kindreds were prospectively recruited from 1995 to 2015. At enrollment, study participants completed medical and family history questionnaires, and provided samples for genotyping. Participants were recontacted between 2015 and 2017 and asked to complete a survey on concerns and experiences related to HP, PRSS1 testing, and genetic counseling. Data were analyzed with descriptive and thematic methods. Thirty‐nine affected participants with HP and 21 unaffected family members completed the survey. Among unaffected family members, 'worry' and 'helplessness' were frequently described as the most difficult problem in their family because of HP, particularly with regard to pain. Three participants described the impact of drug addiction on their family. 'School or work limitations' was the leading financial concern, with 65.5% (36/55) rating it as 'moderately' or 'extremely important.' Unexpectedly, only 62% (21/34) of affected PRSS1 carriers believed the chance for a parent to pass HP to his or her children was 50%, whereas 18% (6/34) believed the chance was 100%. The impact of HP on individuals and families varied, which may reflect the highly unpredictable nature of HP severity and outcomes. Based on current and previously reported findings, an overview of important issues for genetic counselors to consider for counseling HP families is included.